MAGL-18c attenuates LPS-induced sepsis-associated liver injury by inhibiting TGF-β/Smad signaling and remodeling medium- and long-chain fatty acid metabolism - Wang, Ying; Li, Meijia; Liang, Zixia; Wang, Yunyu; Li, Honghua; Li, Shirong; Jiao, Xu; Guo, Na; Dai, Guoxin; Zhang, Guimin; Lu, Xiaoyan; Yao, Jingchun (Frontiers in Immunology, 2026)
IntroductionSepsis is a major global health burden associated with high mortality and multiple organ dysfunction, among which liver injury is a key determinant of poor prognosis. However, effective therapeutic strategies for sepsis-associated liver injury (SALI) remain limited.MethodsIn this study, we investigated the protective effects of MAGL-18c, a novel monoacylglycerol lipase (MAGL) inhibitor, on lipopolysaccharide (LPS)-induced SALI. Hepatic inflammation, apoptosis, mitochondrial function, and lipid metabolism were assessed using liquid chromatography–mass spectrometry (LC-MS), Western blotting, real-time quantitative PCR (qPCR), immunohistochemistry, and other methods.ResultsMAGL-18c markedly attenuated hepatic inflammation by suppressing TGF-β/Smad signaling and reducing pro-inflammatory cytokine production. Moreover, MAGL-18c significantly improved liver histopathology, reduced neutrophil infiltration, modulated unsaturated fatty acid metabolism, and alleviated hepatocyte apoptosis and mitochondrial dysfunction.DiscussionThese findings indicate that MAGL-18c protects against LPS-induced SALI through coordinated regulation of inflammation, apoptosis, mitochondrial function, and lipid metabolism, highlighting its potential as a promising therapeutic candidate for sepsis-associated liver injury.